Relevant methane emission to the atmosphere from a geological gas manifestation - Mazzini, Adriano; Sciarra, Alessandra; Etiope, Giuseppe; Sadavarte, Pankaj; Houweling, Sander; Pandey, Sudhanshu; Husein, Alwi (Scientific Reports, 2021)
Abstract Quantifying natural geological sources of methane (CH 4 ) allows to improve the assessment of anthropogenic emissions to the atmosphere from fossil fuel industries. The global CH 4 flux of geological gas is, however, an object of debate. Recent fossil ( 14 C-free) CH 4 measurements in preindustrial-era ice cores suggest very low global geological emissions (~ 1.6 Tg year −1 ), implying a larger fossil fuel industry source. This is however in contrast with previously published bottom-up and top-down geo-emission estimates (~ 45 Tg year −1 ) and even regional-scale emissions of ~ 1–2 Tg year −1 . Here we report on significant geological CH 4 emissions from the Lusi hydrothermal system (Indonesia), measured by ground-based and satellite (TROPOMI) techniques. Both techniques indicate a total CH 4 output of ~ 0.1 Tg year −1 , equivalent to the minimum value of global geo-emission derived by ice core 14 CH 4 estimates. Our results are consistent with the order of magnitude of the emission factors of large seeps used in global bottom-up estimates, and endorse a substantial contribution from natural Earth’s CH 4 degassing. The preindustrial ice core assessments of geological CH 4 release may be underestimated and require further study. Satellite measurements can help to test geological CH 4 emission factors and explain the gap between the contrasting estimates.